2019
DOI: 10.22437/pim.v7i1.8788
|View full text |Cite
|
Sign up to set email alerts
|

Analisis pengaruh kredit perbankan terhadap pertumbuhan ekonomi Kota Jambi

Abstract: This study aims to: 1) To find out and analyze the development of working capital loans, investment loans, consumer loans and the Economic Growth of the City of Jambi in the period 2002 - 2017; 2) To find out and analyze the effect of working capital loans on the economic growth of the City of Jambi in the period 2002 - 2017; 3) To find out and analyze the effect of investment credit on the economic growth of Jambi City in the period 2002 - 2017; and 4) To find out and analyze the effect of consumer credit on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
1
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
0
1
6
Order By: Relevance
“…Thus, it can be concluded that partially, the growth of consumption financing has a significant effect on economic growth (GDP) in Indonesia. These results contradict the research conducted by Ramadhanty and Auwalin (2021) and Nurjanah and Achmad (2019) which showed that financing in the form of consumption did not have a significant effect on economic growth.…”
Section: The Influence Of the Growth Of Islamic Commercial Banks' Con...contrasting
confidence: 98%
“…Thus, it can be concluded that partially, the growth of consumption financing has a significant effect on economic growth (GDP) in Indonesia. These results contradict the research conducted by Ramadhanty and Auwalin (2021) and Nurjanah and Achmad (2019) which showed that financing in the form of consumption did not have a significant effect on economic growth.…”
Section: The Influence Of the Growth Of Islamic Commercial Banks' Con...contrasting
confidence: 98%
“…Efektivitas transmisi kebijakan moneter beserta dampaknya terhadap bank sentral di negara-negara ASEAN-5 (Indonesia, Malaysia, Filipina, Singapura, dan Thailand) telah banyak dipelajari dalam literatur. Tinjauan pustaka ini mengkaji temuantemuan utama dan didukung oleh kontribusi dari penelitian sebelumnya diantaranya Dwiastuti (2020), Zumaidah & Soelistyo (2018), Maherika et al (2019), Setiawan (2021), Amaliawiati et al (2019, Naz et al (2018), Fufa & Kim (2018), Osabohien et al (2020), Chatziantoniou et al (2021), serta Prihatin et al (2019) melalui studi yang relevan serta implikasinya terhadap kebijakan moneter dan pertumbuhan ekonomi di kawasan ASEAN-5.…”
Section: Kajian Teori Dan Hipotesisunclassified
“…Investasi dapat dipengaruhi oleh penyaluran kredit, dimana investor yang memiliki dana yang kurang akan mendapatkan saluran dana dari masyarakat hingga pada akhirnya akan meningkatkan pertumbuhan ekonomi. Maherika et al (2019) juga menyampaikan bahwa adanya pengaruh yang signifikan dalam penyaluran kredit modal kerja oleh perbankan dalam bentuk pembiayaan pada sektor riil terhadap pertumbuhan ekonomi di Kota Jambi. Dengan adanya kredit modal kerja ini diharapkan mampu mendorong laju pertumbuhan ekonomi.…”
Section: Kredit Modal Kerja Dan Kredit Konsumsiunclassified
“…Penelitian sebelumnya terkait penyaluran kredit dan pertumbuhan ekonomi telah banyak dilakukan. Penyaluran kredit investasi berpengaruh signifikan terhadap pertumbuhan ekonomi di provinsi kalimantan barat (Maherika, Nurjanah and Achmad, 2019;Dwiastuti, 2020). Pembiayaan syariah juga berpengaruh signifikan terhadap pertumbuhan ekonomi (Sudrajat and Sodiq, 2017;Setiawan, 2020).…”
Section: Pendahuluanunclassified